2016
DOI: 10.1038/srep19348
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of a Carnosine-Acrolein Adduct and its Quantification in Human Urine Samples

Abstract: Aldehydes accumulate in inflammation, during myocardial infarction and have been associated with pain symptoms. One pathway of aldehyde detoxification is the conjugation with carnosine. A 3-methylpyridinium carnosine adduct from the reaction of carnosine and acrolein was characterized using extensive spectroscopic measurements. The adduct with urinary concentrations of 1.82 ± 0.68 nmol/mg of creatinine is one of the most abundant acrolein metabolites in urine and opens promising therapeutic strategies for carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Although l-carnosine was not detected in serum, it was easily detectable in the urine as a conjugate with ACR (69). The in vivo RCS-scavenging capacity of l-carnosine was further confirmed by 2 independent studies reporting the presence of covalent adducts between carnosine and lipid peroxidation by-products (e.g., ACR, HNE, HHE) in the urine of human volunteers (70,71).…”
Section: Methodsmentioning
confidence: 79%
“…Although l-carnosine was not detected in serum, it was easily detectable in the urine as a conjugate with ACR (69). The in vivo RCS-scavenging capacity of l-carnosine was further confirmed by 2 independent studies reporting the presence of covalent adducts between carnosine and lipid peroxidation by-products (e.g., ACR, HNE, HHE) in the urine of human volunteers (70,71).…”
Section: Methodsmentioning
confidence: 79%
“…Carnosine contains an amino group of the β-alanyl residue and the imidazole ring of L -histidine, and it also has been reported that it acts in quenching α, β-unsaturated aldehydes synergistically when bound as a dipeptide. Like carnosine, the sulfydryl of NAC provides acceptor site for alkylation, which is beneficial for the cyclization of PM [32] , [33] , [34] . Moreover, the pKa of the imidazole ring is 6.83, which means carnosine has the capacity to inhibit intracellular oxidation under physiological pH conditions [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The recent identification of adducts of carnosine with by-products of aldehyde detoxification (e.g., acrolein) suggests that carnosine may be consumed by sub-products linked with the pathogenesis of diabetes complications, such as exacerbated lipoxidation (Bispo et al, 2016).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%